The Role of Governance and Intellectual Capital in Enhancing Maqashid Sharia Performance of Islamic Banks - Fauzi Permana Putra; Endang Hatma Juniwati (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
This study aims to analyze the optimization of maqashid sharia through the implementation of corporate governance and intellectual capital management in Islamic banking in Indonesia for the period 2013-2022. This research uses descriptive quantitative approach with panel data regression method on eight Islamic banks. The independent variable of corporate governance is proxied by sharia supervisory board size, audit committee size, and self-assessment rating, as well as intellectual capital which includes human capital efficiency, structural capital efficiency, relational capital efficiency, and capital employed efficiency. While the dependent variable is maqashid sharia index. The results showed that audit committee size, self-assessment rating, and human capital efficiency had a significant positive effect on the maqashid sharia index. In contrast, sharia supervisory board size and capital employed efficiency have a significant negative effect. Meanwhile, structural capital efficiency and relational capital efficiency show no significant effect. Simultaneously, all variables have a significant effect on the maqashid sharia index. These findings provide important insights for the development and optimization of maqashid sharia in the Islamic banking sector in Indonesia